POLEMIK AL ZAYTUN DAN POPULISME DALAM MODERASI BERAGAMA JELANG PEMILU 2024 - Rohmah, Nihayatur; Soenjoto, Wening Purbatin Palupi (Institut Agama Islam Ngawi, 2024)
Background to the problem: Based on data from the Central Bureau of Statistics, it was stated that in mid-2023, the population of Indonesia was 278.69 million. There was an increase of 1.09% from the previous year. The increasing number of productive ages led to an explosion of demographic bonuses in Indonesia. The increasing number of people vulnerable to various types of conflict and the most vulnerable and sensitive conflict is religious conflict. The Indonesian government has begun implementing religious moderation as a form of anticipation of religious conflict. The Al Zaytun Indramayu Polemic in West Java is a religious conflict, which is considered to have committed blasphemy in the form of implementing worship at the Al Zaytun Islamic Boarding School which is different from Islamic teachings and is linked to the issue of populism ahead of the 2024 election. This study aims to analyze descriptively the polemic of Al Zaytun, populism in the application of religious moderation ahead of the 2024 election. Research Method: in this study using qualitative methods with a literature review approach and news on digital media. Research Conclusion: Understanding religious moderation in framing the Al Zaytun controversy news is indeed It is inevitable that there will be conflicts, differences in the pattern of worship carried out by the Al Zaytun Islamic Boarding School in the concept of understanding of the Indonesian people who are predominantly Muslim, causing polemics and considered controversy for Muslims who are used to worshiping according to the teachings of the Islamic religion. political intrigue ahead of the 2024 election. Religious moderation is an important thing that must be reviewed if it is linked to the Al Zaytun polemic so that the meaning in implementing religious moderation does not justify teachings that are proven to be contrary to Islamic religious law. Religious moderation mediated in digital space is news that shapes diversity opinions and conflicts that need to be handled by all related parties in a win-win solution. Keywords: Al Zaytun,religious moderation,populism,2024 election